Perbandingan Pengembangan Asuransi Syariah di Indonesia dan Malaysia (Analisis Aliran Mazhab Sejarah dan Law as a Tool of Social Engineering) - Inneke Wahyu Agustin (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
This research discusses the development of Islamic insurance or known as takaful. The focus of discussion on sharia insurance in Indonesia and Malaysia by tracing the history of regulation and the growth of the industry. These two things are compared with the conclusion that you can understand the factors that cause differences in the development of Islamic insurance in Indonesia and Malaysia. With a comparative approach, the conclusion is that Islamic insurance regulations in Indonesia and Malaysia are formed based on the soul of the nation by historical flow of law. Have the same foundation, but Indonesia is slower in responding to regulations. As a result, the growth of the Islamic insurance industry in Indonesia lags behind that of Malaysia. The basic couse is due to the role of law in Indonesia is less responsive because the law acts as a means of social control, for changes in Islamic insurance to be more developed.